Partnerships for a Better Governance of Natural Hazard Risks - Elisa Calliari; Jaroslav Mysiak; Silvia Santato; María Má\~nez Costa (Fondazione Eni Enrico Mattei (FEEM), 2014)
This paper discusses the role played by decentralized, voluntary multi-stakeholder partnerships between public authorities and agencies and/or public authorities and civil society for disaster risk reduction. We pay attention to Public Public Partnerships (PuP), a term coined for public alliances in the early 2000s although arguably building upon community-based natural resource management (CBNRM) and disaster risk reduction (CBDRR), as well as other cooperative initiatives. In many respects PuPs became known as a counterpart of PPPs and quickly spread in public water and health service provision. While the concept of PuPs match to some extent the European Unions efforts to expand horizontal cooperation and collaboration, it appears too narrow to capture the sense of European initiatives. In particular, the strict exclusion of business and commercial undertakings in the essence of PuPs by early scholars is not compatible with the call for truly cooperative multi-governance arrangements. The paper examines the concept of PuP, its objectives and defining characteristics, partners involved and relationship tying them. It then moves to understand to what extent partnerships meant to improve cooperation and coordination have permeated the EU legislation and policies, focusing especially on the role of inclusive governance and territorial cooperation. The analysis is complemented by examples of PuPs addressed in the ENHANCE case studies in which disaster risk reduction plays a role.
Keywords: Q54; Q58; 330; Public-public partnerships; Disaster Risk Reduction; Smart Regulation; Cohesion Policy and Territorial Cooperation; Po River Basin; Jucar River Basin; Wadden Sea; Natural Hazard Partnership